Role of gut microbiota and its metabolites in diabetic cardiomyopathy: from pathogenesis to interventions - Ji, Zheng; Yu, Xinrou; Gu, Haodi; Wang, Ping; Meng, Liping; Lin, Hui; Lv, Haitao (Frontiers in Cardiovascular Medicine, 2025)
Diabetic cardiomyopathy (DCM), a prevalent cardiovascular complication and the principal driver of mortality among patients with diabetes, represents a significant clinical challenge. The gut microbiota, which reside a complex ecosystem within the human intestinal tract, play a fundamental role in host metabolism and systemic physiology. Mounting evidence underscores a critical link between gut microbial dysbiosis, microbial-derived metabolites, and DCM pathogenesis mediated through the gut-heart axis. This comprehensive review systematically synthesizes the current research elucidating the multifaceted interplay between the gut microbiota, their bioactive metabolites (e.g., short-chain fatty acids, bile acids, and branched-chain amino acids), and the development and progression of DCM. By critically evaluating the mechanisms underlying the gut-heart crosstalk, we provide novel insights into the etiopathogenesis of DCM. Furthermore, we evaluated emerging therapeutic strategies aimed at mitigating DCM by targeted modulation of the gut microbiota and their metabolic output, highlighting promising avenues for future research and clinical translation.